2019
DOI: 10.1177/1049909119848148
|View full text |Cite
|
Sign up to set email alerts
|

Associations Among End-of-Life Discussions, Health-Care Utilization, and Costs in Persons With Advanced Cancer: A Systematic Review

Abstract: Background: Aggressive end-of-life (EOL) care is associated with lower quality of life and greater regret about treatment decisions. Higher EOL costs are also associated with lower quality EOL care. Advance care planning and goals-of-care conversations (“EOL discussions”) may influence EOL health-care utilization and costs among persons with cancer. Objective: To describe associations among EOL discussions, health-care utilization and place of death, and costs in persons with advanced cancer and explore variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 50 publications
(217 reference statements)
1
70
1
Order By: Relevance
“…168 Finally, reviews of research manuscripts published between January 2012 and January 2019 show that end-of-life discussions with patients with advanced cancer are associated with greater use of hospice care, greater likelihood of death outside the hospital, as well as less costly end-of-life care. 21 Palliative care among non-Hispanic blacks. Published research in disparities in palliative care is limited.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…168 Finally, reviews of research manuscripts published between January 2012 and January 2019 show that end-of-life discussions with patients with advanced cancer are associated with greater use of hospice care, greater likelihood of death outside the hospital, as well as less costly end-of-life care. 21 Palliative care among non-Hispanic blacks. Published research in disparities in palliative care is limited.…”
Section: Methodsmentioning
confidence: 99%
“…(2019). 21 Between January 2012 and January 2019 Systematic Review of 12 quantitative studies Some studies found evidence that racial minorities were less likely than Whites to have EOL discussions with their health-care providers. Sanders, J. J., et al…”
Section: Impact Of Health Care Coverage On Completion Of Advance Care Planning and Directivesmentioning
confidence: 99%
“…Providers may hesitate to initiate ACP discussions due to concern about causing distress; however, a large prospective study of patients with advanced cancer and family caregivers found that end-of-life discussions with medical providers were not associated with increased risk of depression or worry [ 182 ]. In fact, discussions between patients and providers regarding goals of care were associated with fewer hospital admissions and less aggressive treatment near end-of-life [ 183 , 184 ], which may improve quality of life and reduce financial toxicity [ 185 ]. Bereaved family members also have better psychological adjustment when patients undergo less aggressive treatments near end-of-life [ 182 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bereaved family members also have better psychological adjustment when patients undergo less aggressive treatments near end-of-life [ 182 ]. The majority of research on ACP involves hospitalized patients and those near end-of-life [ 183 , 184 , 185 , 186 ]; however, goals of care can be an ongoing and evolving discussion throughout metavivorship. Further research is needed to determine the optimal timing of ACP discussions for metavivors and their family caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…cadth. ca/ resources/ findingevidence/ strings-attached-cadths-database-search-filters# eco, OVID Expert Searches Health [33][34][35][36][37] Different combinations of search terms and specifications have been tested in regard to their sensitivity for our research question. For each applied modification, the first 100 articles have been evaluated to decide whether the modification is applied or not.…”
Section: Information Sources and Search Strategymentioning
confidence: 99%